KEMAMPUAN BERPIKIR TINGKAT TINGGI DALAM PERKEMBANGAN PEMBELAJARAN MATEMATIKA SMA NEGERI 1 MAUPONGGO - Melkior wewe; Apliana Tamo Inya (Jurnal Ilmiah Mandalika Education (MADU), 2024)
It is important for students to master higher order thinking skills. However, based on the results of a study from PISA in 2018, Indonesia is ranked below the OECD average. One of the reasons for the low PISA test results obtained by Indonesia is the low level of high-order thinking skills. The low level of Higher Order Thinking Ability is due to the fact that in the mathematics learning process students are only taught to memorize, rewrite and do homework or exercises, not to be trained more deeply about their Higher Order Thinking Ability and to solve problems relevant to the material being taught. The method used in this research is to use the literature review method. This study aims to determine the relevant learning methods and can improve students' higher order thinking skills. The writing method used is Literature Review, namely by reviewing previous journals that are relevant to the title and purpose of writing. From the studies that have been carried out, there are three lessons that are in line with the goals of Higher-Level Thinking Skills and can improve Higher-Level Thinking Skills, which include Scientific Learning, Problem Posing Learning Approach, and Problem-Based Learning.